When politics collides with public health: COVID-19 vaccine country of origin and vaccination acceptance in Brazil. Issue 19 (6th May 2021) - Gramacho, Wladimir G.; Turgeon, Mathieu
Highlights: Vaccination uptake and intention to vaccinate is generally high in Brazil. Brazilians are less likely to vaccine when the country of origin of a COVID-19 vaccine is mentioned. Chinese and Russian developed-vaccines are the vaccines most rejected. Current President Jair Bolsonaro is a COVID-19 denier and has specifically expressed negative views about China, the Chinese-developed vaccine and vaccination, in general. Rejection of the Chinese-developed vaccine is particularly strong among those who have positive evaluations of President Jair Bolsonaro. Abstract: This study examines the effect of the country of origin of the vaccine on vaccination acceptance against COVID-19. More specifically, we show how the political context in Brazil has affected acceptance of vaccines produced in China, Russia, the US, and England at the University of Oxford. Our data come from a survey experiment applied to a national sample of 2771 adult Brazilians between September 23 and October 2, 2020. We find greater rejection among Brazilians for vaccines developed in China and Russia, as compared to vaccines from the US or England. We also find that rejection of the Chinese-developed vaccine is particularly strong among those who support President Jair Bolsonaro—a COVID-19 denier and strong critic of China and vaccination, in general.